Harnessing the angiogenic potential of adipose-derived stromal vascular fraction cells with perfusion cell seeding - Gregory Reid; Giulia Cerino; Ludovic Melly; Deborah Fusco; Chunyan Zhang; Oliver Reuthebuch; Giulia Milan; Anna Marsano (Stem Cell Research & Therapy)
Abstract Background The rapid formation and long-term maintenance of functional vascular networks are crucial for the success of regenerative therapies. The stromal vascular fraction (SVF) from human adipose tissue is a readily available, heterogeneous cell source containing myeloid lineage cells, mesenchymal stromal cells, endothelial cells and their precursors, and pericytes, which are important for vascular support. Previous studies showed that seeding SVF cells under perfusion and pre-culturing them on three-dimensional (3D) collagen sponges enhances the vascular cell component in vitro while accelerating vascularization and improving human cell engraftment in vivo compared to static pre-culture. However, generating a perfusion-cultured SVF patch over a 5-day period is both costly and challenging for clinical translation. To overcome these limitations, this study explores a no-pre-culture strategy by comparing perfusion-based seeding with static cell loading on 3D sponges. The hypothesis is that perfusion-based seeding enhances in vivo cell engraftment and angiogenic potential by loading different SVF cell subpopulations onto 3D scaffolds during the seeding process. Methods SVF-cells are seeded onto collagen scaffold using two approaches: a closed system perfusion bioreactor for 18 h or static loading onto the sponge surface. The in vitro cell distribution and baseline cytokine profiles were evaluated. Subsequently, human cell engraftment and differentiation were assessed in vivo using a nude rat subcutaneous implantation model. Analyses included the survival of transplanted human cells, the functionality and maturation of newly formed blood vessels within the SVF-patch. Results Perfusion seeding significantly reduced the number of myeloid cells and achieved uniform spatial distribution across the construct. Vascular endothelial growth factor release was significantly increased following perfusion culture, whereas pro-inflammatory cytokines such as tumor necrosis factor-α and interleukin-1β were decreased. In the short term, perfusion culture enhanced uniform vascularization and SVF cell engraftment in vivo. However, the long-term differences between the perfusion-seeded and static-seeded groups diminished. Conclusion Eliminating the need for prolonged pre-culture offers a feasible and cost-effective strategy for advancing regenerative cell-based therapies by reducing pre-culture times while preserving therapeutic efficacy. Perfusion-based seeding offers significant short-term benefits, including enhanced vascularization and cell engraftment, though long-term differences compared to static seeding are minimal. Further investigation is needed to evaluate its potential in a diseased ischemic heart model. Graphical abstract